1998
DOI: 10.1016/s0020-7292(98)00099-x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent abortion and moderate or strong antiphospholipid antibody production

Abstract: The live birth rate in patients strongly positive for aPL is lower than that in patients with moderate aPL production even if treatment is performed during pregnancy. However, ASA is useful to treat cases with moderate aPL so that distinction of the two groups is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Of these 46, 26 were aPE-positive, and of the 21 who produced IgG aPE, only one had a successful next pregnancy. A successive report from this institution assayed for aPE by ELISA, but did not differentiate aPE-positive patients from other aPL-positive patients [41].…”
Section: Ape and Clinical Pathology Associationsmentioning
confidence: 91%
“…Of these 46, 26 were aPE-positive, and of the 21 who produced IgG aPE, only one had a successful next pregnancy. A successive report from this institution assayed for aPE by ELISA, but did not differentiate aPE-positive patients from other aPL-positive patients [41].…”
Section: Ape and Clinical Pathology Associationsmentioning
confidence: 91%
“…Medication with low-dose aspirin (40 mg/ day) had been started from 10 weeks of gestation in the previous study [9].…”
Section: Case Reportmentioning
confidence: 99%
“…An investigation of Barbui et al 68 indicated a high incidence of LA (positive in 14% of women with abortions). Ogasawara et al 24 found the prevalence of antibodies to be 5.4% IgG and IgM antibodies and 11.3% for LA. Similar results were reported by Soltesz et al 69 with 14.5% LA and 26.1% IgG antibodies alone and 39.0% IgM antibodies alone, respectively, and both antibodies together in 20.3%.…”
Section: Discussionmentioning
confidence: 98%
“…17 The relationship between APS and pregnancy complications including fetal loss has been reviewed recently. [18][19][20][21][22][23] Ogasawara et al 24 found a failure rate of 19.4% after standard therapy. Tincani et al 25 found a complication rate of more than 20%, although standard therapy was associated with a premature birth rate of up to 18.8%, preeclampsia with 11.6%, and intrauterine growth retardation or restriction (IUGR) of 6%.…”
mentioning
confidence: 99%